IMPACT ASSESSMENT OF NIELSEN AS A RESEARCH FIRM USING EDITORIAL ONLINE MEDIA - Masih, Jolly; Chauhan, Sonalee (British Journal of Marketing Studies, 2015)
Online media is revolutionising the world through it new creative outputs and thus condensing entire world into a global village. Users of online media are increasing many folds every year. Online media mainly consist of Editorial media (online newspaper editions, journals, publication house, magazines) and Social media (Facebook, Twitter, Reviews and Forums, Youtube, Pininterest etc.). Online media is not only the source of branding and advertising but also a major source to create an impact and impression in minds of Readers/users. Nielsen is leading marketing research and information firm with nearly 34,000 employees in 100+ countries around the world. Nielsen is aggressively using online media to create a positive impact on the masses about their surveys, researches and other services. 5 major keywords performance (KPI’S) indicators namely Innovation, Consumer Study (what consumer buy and watch), Global provider, Insights and Spokesperson were being used for impact assessment. Entire data bulk was being divided in 4 tiers (levels) based on impact factor of the journal/publications. A modified Harvard tool called “Popping impressions” was being used to assess the effectiveness of KPI’S. Impact was assesed on basis of presence of keywords in articles which refers to exact or similar meaning of that particular KPI. 714 articles from different newspaper editions, journals, publication house, and magazines were being assessed. Studies showed that performance of KPI’S differed at each Tier. At Tier 1 and 4 Insights has made maximum impact of 12.7% and 7.6% respectively as major KPI. Consumer study ruled as major KPI with values of 13% and 19.2% respectively for Tier 3 and 4.